2020
DOI: 10.3389/fphar.2020.574176
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of High-Altitude Hypoxia on the Transcription of CYP450 and UGT1A1 Mediated by PXR and CAR

Abstract: Little is known about what roles the pregnane X receptor (PXR) and constitutive androstane receptor (CAR) play in drug metabolism in high-altitude hypoxia. Likewise, the potential interaction of nuclear receptors and drug metabolism enzymes during drug metabolism of high-altitude hypoxia is not fully understood. In this work, we investigated the effects of high-altitude hypoxia on transcriptional regulation of cytochrome P450 (CYP450) and UDP-glucuronosyltransferase 1A1 (UGT1A1) genes mediated by PXR and CAR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
(56 reference statements)
3
8
0
Order By: Relevance
“…Studies have shown a strong link between PXR and MDR1 Gu et al, 2013). Previous studies by the authors have demonstrated a significant reduction of PXR expression in rats and HepG2 cells under hypoxic conditions (Duan et al, 2020). This study showed that the expression of PXR in Caco-2 cells under hypoxic conditions was also reduced significantly, which is in line with the previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies have shown a strong link between PXR and MDR1 Gu et al, 2013). Previous studies by the authors have demonstrated a significant reduction of PXR expression in rats and HepG2 cells under hypoxic conditions (Duan et al, 2020). This study showed that the expression of PXR in Caco-2 cells under hypoxic conditions was also reduced significantly, which is in line with the previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Drug metabolizing enzymes and transporters are the main factors affecting drug metabolism. In our previous studies, we found that high-altitude hypoxia affects the activity and expression of cytochrome P450 (Duan et al, 2020;Duan et al, 2021;Zhou et al, 2018). To date, only a few reports have addressed the ways to resolve the problem of changes in the functions and expression levels of drug transporters under high altitude hypoxic environments.…”
Section: Discussionmentioning
confidence: 88%
“…20,21 Moreover, PXR has been approved to play an anti-inflammatory role by inhibiting the actions of the NF-κB signaling pathway 22−24 and hypoxia can potently inhibit the expression of PXR. 25 Therefore, we hypothesize that PXR is involved in the protective effect of IPA on BBB.…”
Section: ■ Resultsmentioning
confidence: 97%
“…( 20 , 25 ). The primers used were: (1) cyp3a4 , forward sequence 5’-CCGAGTGGATTTCCTTCAGCTG-3’, reverse sequence 5’-TGCTCGTG GTTTCATAGCCAGC-3’; (2) β-actin , forward sequence 5’-CACCATTGGCAATGA GCGGTTC-3’, reverse sequence 5-AGGTCTTTGCGGAT GTCCACGT-3’; (3) PXR/NR1I2 ( 31 ), forward sequence 5’-CCCACCTCAGA AGACAAAGC-3’, reverse sequence, 5’-GAACCCCAGACCCTACACAA-3’ ( 4 ); CAR/NR1I3 ( 31 ): forward sequence, 5’-TACTGTGCTTCGTGCTCCTG-3’, Reverse sequence, 5’-CCTGG TCTTCGGGTTCAAG-3’. The results (the relative expression level [folds of β-Actin]) of PXR or CAR was shown as heat-map.…”
Section: Methodsmentioning
confidence: 99%